Arylsilane oxidation - new routes to hydroxyated aromatics - Bracegirdle, S; Anderson, E (RSC Publishing, 2010)
An efficient route to hydroxylated aromatics has been developed, via the oxidation of aryl organosilanes under functional group-tolerant and relatively mild conditions, using sub-stoichiometric amounts of fluoride promoters.